Diabetes Mellitus & Thyroid Dysfunction in Vitiligo of Terai Regions of Nepal - Gurung, Sabhyata; Shrestha, Pratistha; Shrestha, Meera; Panday, Shrikant; Chhetri, Pradip (Journal of Universal College of Medical Sciences, 2023)
INTRODUCTION Vitiligo is common acquired disease. Clinically it present with depigmented, macules and patches. Vitiligo has been shown association with many autoimmune diseases like Diabetes mellitus, Thyroid disorders, Graves disease, pernicious anemia, etc. This study was undertaken to assess the prevalence and association of diabetes mellitus and thyroid dysfunction in vitiligo patient. MATERIAL AND METHODS This study was a case control study carried out in Dermatology Department, Universal College of Medical Sciences – Teaching Hospital (UCMS-TH) from Dec 2022 to Nov 2023. 70 cases of Vitiligo and 70 control with same sex, ages and gender matched were enrolled. All patients in both the group, we performed thyroid function test and fasting blood sugar. RESULTS Out of 70 cases, 6 (8.6%) people has impaired FBS and 6 (8.6%) people have high T3 & T4 and 10 (14.3%) people have high TSH whereas 3 (4.3%) people have low T3 & T4 and 4 (5.7%) people have low TSH. Association with different age group in both case and control group with fasting blood sugar and thyroid function test was seen which was statistically not signiﬁcant. CONCLUSION There were impaired fasting blood sugar and abnormal thyroid dysfunction in many cases. Therefore vitiligo patient needs to undergo thyroid function test and blood sugar level to prevent the complication.